Chronic paracetamol treatment induces neuroinflammation and microglia activation in rat hippocampus - Lalert, Laddawan; Ruangvejvorachai, Preecha; Maneesri-le Grand, Supang (Chulalongkorn Medical Journal, 2021)
Background: Several studies have demonstrated multidirectional effects of paracetamol (acetaminophen; APAP) treatment on the central nervous system. Recently, an alteration of learning and memory have been reported following long-term APAP exposure; however, the mechanism underlying these detrimental effects of APAP treatment is not fully clarified. Objectives: To investigate the effect of chronic APAP treatment on the microglia activation and neuroinflammation in the hippocampus. Methods: Male Wistar rats (weighting 250 - 300 g) in the APAP-treated group was once a day gavaged with 200 mg/kg bodyweight APAP for 30 days, while distilled water at the same volume was orally delivered to the rats in the control group. Expression of pro-inflammatory cytokines was evaluated using Western blotting analysis, while the ionized calcium-binding adaptor molecule 1 (Iba-1) and nuclear factor erythroid-2-related factor 2 (Nrf2) protein expressions were determined by using immunohistochemistry and immunofluorescence, respectively. Results: As compared with the control rats, the expression of tumor necrosis factor-alpha (TNF-alpha) and interleukin-1beta (IL-1beta) were significantly higher in the APAP-treated rats then in the control rats. A significant increase in Iba-1 protein was demonstrated in rats with 30-day APAP exposure. In addition, an increment of Nrf2 protein expression was also observed in the APAP-treated group. Conclusion: The present results suggest that chronic APAP treatment can induce microglia activation and upregulation of proinflammatory cytokines in the hippocampus. An increment of the Nrf2 expression may involve neuroinflammatory response following prolonged treatment with APAP.